The delamination effect of drilling and electro-discharge machining on the tensile strength of woven composites as studied by X-ray computed tomography. (2016) - Korlos, Apostolos; Tzetzis, Dimitrios; Mansour, Gabriel; Sagris, Dimitrios; David, Constantine
The presence of stress concentration especially from any induced delamination around a hole causes substantial perturbation of the stress and strain field in the structure under service loads. Therefore, it is of great practical interest to accurately analyse and quantify any delamination and its effect to the load bearing capacity of the structure. Two types of open-hole machining - drilling and electro-discharge machining (EDM) - were applied in order to examine their effect on the tensile strength of carbon/epoxy laminates. Pulse durations of 100 µs 200 µs and 300 µs with a current of 3 A and voltage 100 V were used for the EDM. An X-ray computed tomography (CT) was employed to examine the delaminations; while three delamination factor models provided the measuring quantities for assessment. An infrared thermography was used for monitoring the fracture behaviour of the carbon/epoxy open-hole specimens during tensile testing. A finite element model (FEM) computed the stress concentrations around the holes; while the Whitney-Nuismer point stress criterion employed successfully in order to predict the failure strengths of the laminates. The results indicate that the CT process is a very effective tool for capturing the delaminations from open-hole machining and showed that the 100 µs pulse duration induce lower delaminations; slightly comparable with the ones of the drilling procedure.